Molecular mechanisms of isoniazid resistance in Mycobacterium tuberculosis and Mycobacterium bovis. - Rouse, D A (1995)
Genetic and biochemical studies have suggested a link between reduced catalase activity and resistance to isoniazid in Mycobacterium tuberculosis. In this study, we examined the molecular mechanisms of resistance to isoniazid with six in vitro mutants of the M. tuberculosis complex (Mycobacterium bovis and M. tuberculosis). Five of six mutants resistant to isoniazid were negative by catalase assays. Immunoblot analyses using a polyclonal antibody against the katG gene product (catalase-peroxidase) demonstrated that the enzyme is not produced in four of these isoniazid-resistant strains. A complete deletion of the katG gene was detected in only one of these isoniazid-resistant M. tuberculosis complex strains by Southern blot analyses. In two other resistant strains, partial deletions of the katG gene were identified. A point mutation which resulted in the insertion of a termination codon in the katG coding sequence caused a catalase-negative phenotype in a fourth strain. Of the two resistant strains which produce the enzyme, one was shown to be negative by a catalase assay. Single-stranded conformational polymorphism and DNA sequence analyses identified a mutation in the katG gene of this strain which may contribute to reduced enzymatic activity and subsequent isoniazid resistance. These data demonstrate that genetic alterations to the katG gene other than complete deletions are prevalent and may contribute significantly to the number of cases of isoniazid-resistant tuberculosis.